The emotional underpinning of norms and identities in framing Korean aid. Issue 3 (3rd April 2023) - Noh, Jae-Eun
ABSTRACT: While evidence is growing in relation to emotions in international relations, emotions in aid policy have been little researched. Emotions can deepen the understanding of national norms and identities, in which aid policies are grounded. Korea is establishing its norms and identities as a non-traditional donor. This article explores Korean aid, focusing on emotions as presented and circulated in publicly available documents produced by governmental aid agencies, civil society, and news media. The findings confirm that the identified emotions – including national pride, the sense of global responsibility, and friendship – reflect and construct Korean aid norms and identities. This study suggests the role of emotions in consolidating conflicting norms, shaping a unique donor identity, and building public awareness and support. This study extends the current understanding of Korean aid by highlighting the need for more attention to the emotions in aid policies.